Los exilios venezolanos en México y Costa Rica durante el siglo XX - Cervantes-Varela, Andrés (2017)
This article aims to outline a chapter of the history of Latin American exile that has not been investigated yet: the life and activities of groups of Venezuelan citizens who between 1928 and 1935 and between 1948 and 1958 were opponents or victims of governments which came to national power backed by powerful domestic and foreign economic interests. These citizens, as opponents of those governments, found security and opportunities to leave Venezuela mainly towards two countries: Mexico and Costa Rica. México and Costa Rica were the largest recipients and protectors of those Latin American exiles persecuted by authoritarian governments during the twentieth-century.